Transformasi tata kelola keuangan berbasis enterprise resource planning: Studi kasus implementasi Sistem Kanadi pada Dealer Honda Nusantara Sakti Manado - Alfa Pratama Kaempe; Hendrik Gamaliel; Lady Diana Latjandu (Manajemen Bisnis dan Keuangan Korporat, 2026)
Enterprise Resource Planning (ERP) adoption has been extensively studied in large manufacturing and multinational enterprises; however, empirical evidence from regional automotive retail dealerships in developing economies remains scarce. This study aims to examine the role of the Kanadi system—a proprietary, web-based ERP platform—in supporting financial performance at Honda Nusantara Sakti dealership in Manado, Indonesia, by analyzing its operational mechanisms, internal control functions, and contribution to managerial decision-making quality. A qualitative descriptive research design was employed. Data were collected through semi-structured in-depth interviews with the Head of Administration as the purposively selected key informant, passive participatory observation of daily financial workflows, and triangulated document analysis of internal SOP records, transaction archives, and system usage logs. Data were analyzed through thematic coding and cross-validated via source and method triangulation. The findings reveal that the Kanadi system supports financial performance through three interconnected mechanisms: (1) operational efficiency, realized through cross-divisional data integration that eliminates redundant data entry, accelerates the financial book-closing cycle, and enables real-time transaction processing; (2) data reliability, reinforced by biometric fingerprint authorization, centralized internal controls, and mandatory daily reconciliation protocols that achieved near-perfect transaction accuracy; and (3) managerial decision-making quality, facilitated by real-time financial dashboards enabling continuous monitoring of liquidity positions, collection rates, and daily sales target attainment. Operational constraints persist, particularly internet connectivity instability inherent to web-dependent ERP architecture and residual human input error risks, which are mitigated through a responsive internal IT helpdesk and structured employee onboarding programs. This study extends the ERP effectiveness literature beyond conventional manufacturing contexts by providing empirical evidence from a regional automotive retail setting in a developing economy, offering theoretical and practical contributions for dealership management, ERP system designers, and digital financial governance policymakers.